2015
DOI: 10.1128/aac.00525-15
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Predictors, and Impact on Hospital Mortality of Amphotericin B Nephrotoxicity Defined Using Newer Acute Kidney Injury Diagnostic Criteria

Abstract: bStudies on amphotericin B (AmB) nephrotoxicity use diverse definitions of acute kidney injury (AKI). Here, we used the new Kidney Disease Improving Global Outcome (KDIGO) system to describe the incidence, predictors, and impact of AmB-induced AKI on hospital mortality in 162 patients treated with AmB (120 with deoxycholate preparation and 42 with liposomal preparation). KDIGO stage 1 requires an absolute increase of >0.3 mg/dl or >1.5؋ over baseline serum creatinine (SCr), while stage 2 requires >2؋, and stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
16
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
3
16
2
Order By: Relevance
“…Our group has recently shown that the use of newer AKI diagnostic criteria (RIFLE, AKIN, and KDIGO) is able to shorten the time to detection of AmB-induced AKI compared to the use of traditional criteria (34). Herein, we showed that determination of the UrNGAL level has the potential to detect AmB-induced AKI even earlier than use of the most sensitive of the newer SCr-based (KDIGObin) criteria.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Our group has recently shown that the use of newer AKI diagnostic criteria (RIFLE, AKIN, and KDIGO) is able to shorten the time to detection of AmB-induced AKI compared to the use of traditional criteria (34). Herein, we showed that determination of the UrNGAL level has the potential to detect AmB-induced AKI even earlier than use of the most sensitive of the newer SCr-based (KDIGObin) criteria.…”
Section: Discussionmentioning
confidence: 75%
“…In our recent retrospective study, we showed that the increase in sensitivity of the KDIGObin criterion for the detection of AmBinduced AKI was accompanied by a loss of specificity and the ability to predict hard outcomes, such as intensive care unit admission or mortality (34). Therefore, future studies should be conducted to evaluate if a UrNGAL-oriented treatment strategy will result in a reduction in the incidence of AmB-induced AKI (as defined by SCr-based criteria), as well as reductions in lengths of hospital stay and costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] The use of lipid-based formulations reduces the prevalence of AB-induced nephrotoxicity to between 9% and 25%. [70][71][72] (a) Efficacy Rank probabilities sum to one, both within a rank over treatments and within a treatment over ranks. Each drug has a probability of being the best treatment (rank 1) or the worst treatment (rank 5).…”
Section: Discussionmentioning
confidence: 99%
“…Two retrospective Brazilian studies have also examined the incidence of L-AMB nephrotoxicity in mixed patient populations using either the RIFLE criteria (8) or the more sensitive Kidney Disease Improving Global Outcome (KIDGO) staging criteria (16). Of the two, the study by Falci et al (8) is more applicable to our analysis, as they included 105 patients treated with L-AMB and found 22% of the patients fell into the risk category, 3.7% progressed to injury, and 2.4% developed failure.…”
Section: Discussionmentioning
confidence: 99%